Bacterial Infections Transmitted by Ticks in Barnaul: Epidemiological and Epizootological Situation, Diagnostic Problems - Chekanova, T. A.; Rakov, A V.; Petremgvdlishvili, K.; Timonin, A. V.; Lukyanenko, N. V.; Safyanova, T. V.; Shirokostup, S. V.; Lukyanenko, N. Ya; Kalinina, U. V.; Pashchenko, I. G. (Èpidemiologiâ i vakcinoprofilaktika (Online), 2024)
Relevance. The Altai Кray with its administrative center, Barnaul, is an endemic region for tick–borne rickettsioses. The contribution of other tick-borne infections (TBI) to the structure of overall morbidity in the subject is significantly lower. To assess the risks of complication of the epidemiological situation for bacterial TBI (tick-borne rickettsioses, borrelioses, human granolucytic anaplasmoses, human monocytic ehrlichiosis, coxiellosis) and understand the level of their diagnosis in the region, it is important to study the occurrence of their pathogens in ticks, comparing them with the officially registered incidence. The aim is the study of the epidemiological and epizootological situation in Barnaul for bacterial tick-borne infections as well as an analysis of the factors influencing the registration of the incidence of these infections. Materials and methods. The materials were official statistical reporting data, information, analytical materials, accounting and reporting documentation of the Department of Rospotrebnadzor and the Ministry of Health of the Altai Region. The infection of ticks collected in the biotopes of Barnaul with different landscapes by pathogens of tick-borne encephalitis, human granulocytic anaplasmosis (HGA), human monocytic ehrlichiosis (HME), borrelioses, rickettsioses, and Q fever were studied using molecular biological methods. The species of Rickettsia were determined by Sanger sequencing followed by phylogenetic analysis. Results. Rickettsia conorii subsp. raoultii detected in the Dermacentor ticks with a high occurrence (61.9%), DNA of R. helvetica detected in the Ixodes ticks (5.1%). R. sibirica was not been detected. The infection rate of ticks by Borrelia burgdoferi s.l. was 27.8%; 5.1% of imagos contained B. miyamotoi DNA. Pathogens of HGA, HME were founded in 6.2%, 1.0% of individuals of Ixodes ticks, respectively. In two copies out of 300, the causative agent of Q fever identified. The dynamics of the number of people affected by tick bite over the period 2014-2023 did not tend to decrease, and against this background, there is a continuing high incidence of Siberian tick typhus, in contrast to the incidence of borreliosis. Other bacterial TBI have not been noted in Barnaul officially. Conclusions. In Barnaul, high risks of complications of the epidemiological situation of ixodic tick-borne borreliosis (including non-erythemic forms) have identified, and underdiagnosis of the disease is likely. The question of the etiological structure of tick-borne rickettsiosis, the occurrence of infected individuals with an atypical picture remains unknown. The difficulty of diagnostic of tick-borne rickettsiosis without rash is aggravated by the shortage of reagent kits, primarily for the detection of specific antibodies. The landscape confinement of Dermacentor and Ixodes ticks should take into account when organizing long-term stationary observation sites for monitoring and forecasting the epidemiological and epizootological situation. The risks of Barnaul population infection by HGA, MECH and Q fever pathogens were also noted. Special attention should be paid to the introduction into clinical practice of reagent kits for complex laboratory verification of tick-borne infections.